Prototipe Monitoring Controling Suhu dan Kelembaban Pada Kandang Ayam Petelur Berbasis Internet Of Things (IoT) - Alfariz, M Adam; sumpena, Sumpena (Universitas Dirgantara Marsekal Suryadarma, 2025)
Controlling temperature and humidity is a critical aspect of layer chicken management, as uncontrolled environmental fluctuations can increase stress levels, reduce comfort, and negatively affect productivity. In practice, most farmers still rely on manual monitoring methods, which are unable to respond quickly to rapidly changing conditions. This study aims to develop and evaluate a prototype Internet of Things (IoT)-based monitoring and controlling system for regulating temperature and humidity in layer chicken cages using a NodeMCU ESP8266, a DHT22 sensor, and the Home Assistant platform for real-time monitoring and automated actuator control. Experimental testing was conducted in both open and closed environments to assess sensor accuracy and system effectiveness. Data were collected at 5-minute intervals. The results show that the DHT22 sensor demonstrates low error rates, with temperature errors ranging from 0–2.00% in closed environments and 0.32–0.64% in open environments, while humidity errors range from 0.26–1.17%. The automated control system effectively maintained cage temperature near the ideal range (±32°C), increasing temperature by 2.6–4.3°C under cooler conditions and decreasing temperature by 1.8°C during hotter periods. For humidity control, the system increased humidity levels by 1–3% as required These findings indicate that the developed IoT-based system provides fast response, stable performance, and high accuracy in maintaining environmental conditions within the optimal range for layer chickens, offering a more efficient solution compared with conventional methods. This study contributes a novel application of Home Assistant as a centralized control platform, which remains rarely explored in similar research.